JAMAICA’S STRATEGY IN UTILIZING BOB MARLEY AS SOFT DIPLOMACY IN CULTURAL AND ECONOMIC SECTORS - Rahmat Ardhi Gunawan (HI 16 UMY 098, 2016)
*98 This undergraduate thesis analyzes the Jamaica strategies in utilizing Bob Marley in cultural and economic sectors. The purpose of this research is to explain the strategy of Jamaica in building the cultural and economic sector by utilizing Bob Marley as Soft Diplomacy. It is one of requirements to obtain undergraduate title from International Program of International Relations, Social and Political Science Faculty, Muhammadiyah University Yogyakarta. This research uses the concept of cultural diplomacy by K.M. Panikkar and the concept of strategy by Christiance. The methodology of research is library research method, to collect the data using literatures method, from books, newspapers, journals and magazines, internet, and other literatures sources. This thesis uses descriptive analysis to see the effort of Jamaica government itself. .Keywords : Jamaica, Bob Marley, Reggae, Soft Diplomacy, Jamaica Culture, Jamaica Economy.